Do motoneuron discharge rates slow with aging? A systematic review and meta-analysis. (April 2022) - Orssatto, Lucas B.R.; Borg, David N.; Pendrith, Linda; Blazevich, Anthony J.; Shield, Anthony J.; Trajano, Gabriel S.
Abstract: Nervous system maladaptation is linked to the loss of maximal strength and motor control with aging. Motor unit discharge rates are a critical determinant of force production; thus, lower discharge rates could be a mechanism underpinning maximal strength and motor control losses during aging. This meta-analysis summarized the findings of studies comparing motor unit discharge rates between young and older adults, and examined the effects of the selected muscle and contraction intensity on the magnitude of discharge rate difference between these two groups. Estimates from 29 studies, across a range of muscles and contraction intensities, were combined in a multilevel meta-analysis, to investigate whether discharge rates differed between young and older adults. Motor unit discharge rates were higher in younger than older adults, with a pooled standardized mean difference (SMD) of 0.66 (95%CI= 0.29–1.04). Contraction intensity had a significant effect on the pooled SMD, with a 1% increase in intensity associated with a 0.009 (95%CI= 0.003–0.015) change in the pooled SMD. These findings suggest that reductions in motor unit discharge rates, especially at higher contraction intensities, may be an important mechanism underpinning age-related losses in maximal force production. Highlights: The force produced by a muscle depends on the rate its motor unit's discharges. We observed lower motor unit discharge rates in older than in younger adults. The age-related discharge rate differences are augmented at stronger contractions. The between-muscle differences in motor unit discharge rates remain unclear. Slower discharge rates may partially underpin the age-related loss in strength.